2015
DOI: 10.1186/s13075-015-0894-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of RasGRP1 in rheumatoid arthritis and modulation of RasGRP3 as a biomarker of TNFα inhibitors

Abstract: BackgroundB and T cells play a key role in rheumatoid arthritis (RA) pathophysiology. RasGRP1 and RasGRP3 are involved in T and B cell receptors signaling, and belong to gene combination able to predict infliximab responsiveness, leading to the question of RasGRP1 and RasGRP3 involvement in RA.MethodsRasGRP1 and RasGRP3 expression levels were measured by qRT-PCR and/or western-blot in peripheral blood mononuclear cells (PBMCs), in T and B cells from untreated RA patients and in RA patients treated by TNFα inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…A recent study reported a heterozygous mutation in RASGRP1 correlated with autoimmune lymphoproliferative syndrome (ALPS)-like disease (17). RASGRP1 expression in T-cells also correlated negatively with rheumatoid arthritis disease activity (18). Dysregulated expression of RASGRP1 has been observed in human SLE.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a heterozygous mutation in RASGRP1 correlated with autoimmune lymphoproliferative syndrome (ALPS)-like disease (17). RASGRP1 expression in T-cells also correlated negatively with rheumatoid arthritis disease activity (18). Dysregulated expression of RASGRP1 has been observed in human SLE.…”
Section: Introductionmentioning
confidence: 99%
“…A polymorphism (Arg 519 Gly) in Rasgrp1 in mice results in T cell abnormalities and autoimmunity ( Daley et al, 2013 ). Furthermore, several genetics studies have linked single nucleotide polymorphisms (SNPs) in RasGRP1 to human autoimmune disease ( Plagnol et al, 2011 ; Qu et al, 2009 ), and low RasGRP1 levels have been detected in T lymphocytes from patients with Systemic Lupus Erythematosus (SLE) ( Yasuda et al, 2007 ), and rheumatoid arthritis (RA) ( Golinski et al, 2015 ). Complete RasGRP1 deficiency in a patient leads to a novel primary immunodeficiency, with impaired activation and proliferation of the patient's T- and B- cells and defective killing by cytotoxic T cells and NK cells ( Roose, 2016 ; Salzer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other genes, TNPO2 and WDR83, were related to tumor development. One region on ECA1 harbored the gene RASGRP1, which was found in common between ROH and iHS and plays a key role in the development of T and B cells [40]. Studies have associated RASGRP with disease phenotypes in bovine animals [41,42] and dogs [43].…”
Section: Discussionmentioning
confidence: 99%